Crete - Gauldie, Robin; Gale Group (New York DK Publishing, 2015)
Provides background information on the Greek island of Crete; recommends the 10 best restaurants, bars, hotels, entertainment, and outdoor activities, along with information on trip planning, nightlife, and shopping.
Crete's top 10 -- Around the island -- Streetsmart.
Includes bibliographical references and index.
Keywords: Crete (Greece) -- Guidebooks